2010
DOI: 10.1021/es1022653
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Hydrocarbon Biodegradation under Seasonal Freeze−Thaw Soil Temperature Regimes in Contaminated Soils from a Sub-Arctic Site

Abstract: Several studies have shown that biostimulation in ex situ systems such as landfarms and biopiles can facilitate remediation of petroleum hydrocarbon contaminated soils at sub-Arctic sites during summers when temperatures are above freezing. In this study, we examine the biodegradation of semivolatile (F2: C10-C16) and nonvolatile (F3: C16-C34) petroleum hydrocarbons and microbial respiration and population dynamics at post-and presummer temperatures ranging from -5t o1 4°C. The studies were conducted in pilot-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Diesel degradation and bacteria in Arctic soils TH Bell et al Hydrocarbons in Soil, as used previously for the determination of hydrocarbon concentrations in sub-Arctic soils (Chang et al, 2011). Detailed procedures for soil and hydrocarbon analyses are presented in the Supplementary Material.…”
Section: Soil Collection and Analysesmentioning
confidence: 99%
“…Diesel degradation and bacteria in Arctic soils TH Bell et al Hydrocarbons in Soil, as used previously for the determination of hydrocarbon concentrations in sub-Arctic soils (Chang et al, 2011). Detailed procedures for soil and hydrocarbon analyses are presented in the Supplementary Material.…”
Section: Soil Collection and Analysesmentioning
confidence: 99%
“…In particular research on permafrost soil bioremediation is at present under-represented, with only a few studies available on the topic61521. In previous works1522 we used a 16 S rRNA gene pyrosequencing approach to describe the bacterial biodiversity of uncontaminated/contaminated deep active layers and upper permafrost (i.e.…”
mentioning
confidence: 99%
“…The intrinsic halotolerance of cold‐tolerant bacteria and its relevance to microbial survival mechanisms in cryohabitats have been suggested previously in fundamental research on bacteria in cold habitats, which include the eutectic interface associated with brine‐filled veins, pockets and networks in sea ice and water . Other cold‐region studies have reported significant hydrocarbon biodegradation activity in frozen sub‐Arctic soils at subzero temperatures . Cold‐adapted hydrocarbon‐degrading bacteria that can survive in moderate salinities (<2.5% NaCl), as well as the hydrocarbon degradation associated with their activity, have also been frequently reported .…”
Section: Resultsmentioning
confidence: 83%
“…The soils from the Northwest Territories and Resolution Island are denoted as NW and RI soils, respectively. Hydrocarbon‐degrading bacteria are abundant in both soils . The detailed properties of the NW and RI soils were characterized in previous studies by the current authors .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation